Complicaciones postquirúrgicas en pacientes caninos con ruptura de ligamento cruzado craneal - Valenzuela Oliva, Solange (2024)
Cranial Cruciate Ligament Rupture (CrCL) is one of the most common orthopaedic pathologies in canines. The objective of this study was to report the complications that occur in canine patients with CrCL treated with an extra-articular stabilization technique. The age, breed and weight of the dogs and their possible relationship with any post-surgical complications were considered. Surgical procedures were based on the description of Flo (1975). Complications were classified as catastrophic, moderate and mild. Clinical data of 80 canines were used, where 7 (8.75%) presented postsurgical complications, 5 presented moderate complications (71.4%) and 2 patients presented mild complications (28.6%), while 73 (91.25%) of patients did not present complications in their recovery. The presentation of CrCL was significantly higher (p<0.001) in adult canines and in patients with a body weight greater than 15 kg (p<0.001).